EARLY DETECTION OF BREAST AND CERVICAL CANCER OF THE RESIDENTS OF PROPPO PAMEKASAN DISTRICT - Dyah Fauziah; Alphania Rahniayu; Nila Kurniasari; Anny Setijo Rahaju; Etty Hary Kusumastuti; Gondo Mastutik; I Ketut Sudiana (Universitas Airlangga, 2021)
Introduction: Breast cancer and cervical cancer are common cancers in females. Both of these cancers can be detected early. Early detect vion can reduce cancer morbidity and mortality. The community outreach activities are required to increase knowledge about breast cancer and cervical cancer, in addition to screening as preventive efforts for these two cancers.Methods: The activity of raising knowledge about the prevention and early detection of breast cancer and cervical cancer was carried out through community counseling to 94 females who were members of the PKK and young females in the Kecamatan Proppo, Kabupaten Pamekasan. Pre and post tests were given before and after the community counseling. After the community counseling, 86 participants were screened for breast cancer by clinical palpation and 46 participants were screened for cervical cancer using the pap smear method.Results: The result of the post test showed a 27.53% increase in knowledge. The results of the pap smear examination on participants showed 96% concluded as Papanicolau Class II, 2% Class I, and 2% Class IV. The patient with class IV results was referred to an obstetrician.Conclusion: Community counseling about breast self examination (BSE) and Pap smear can increase people's knowledge about early detection of breast cancer and cervical cancer.